Development and Validation of a Method for Preclinical Durability Evaluation of Linked Semiconstrained Total Elbow Replacement Prostheses. (February 2019) - Varadarajan, Ravikumar; Kincaid, Brian L
Total elbow replacement (TER) is a clinically successful procedure yet isolated, gross mechanical complications associated with implant durability persist. The objectives of this study were to (1) develop a clinically relevant in vitro methodology to replicate the reported damage modes and (2) demonstrate durability improvements of a next-generation linked, semiconstrained design. Two TER prostheses were tested on a biaxial test frame at 1.4 Hz in 37 ± 3° deionized water through 0° to 130° flexion/extension at various load levels simulating high demand, posttraumatic patients until either component failure or run out to 200 000 cycles. The damage patterns of tested components were qualitatively compared to retrieved components to establish the clinical validity of the methodology. The run out load of design 1 was equivalent to 100 N weight in hand (WIH). Specimens tested at higher load levels exhibited multimodal damage consistent in appearance with the clinical literature. The minimum run out load of design 2 was 110 N WIH with no significant damage observed on the components. The methodology developed here was shown to reproduce the clinical damage modes associated with TER in high demand, posttraumatic patients. The method was able to distinguish performance differences within and between 2 different linked, semiconstrained designs.